Visual Outcome of PRK and Lasik: Five Year Followup - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2007)
Purpose: To evaluate the visual outcome of PRK and Lasik in age and refractive error matched eyes. Material and Methods: This retrospective study was conducted on the fifth year follow up of the refractive surgery patients who have under gone photorefractive keratectomy (PRK) and laser in situ keratomileusis (Lasik) procedures for moderate degree of myopia. One surgeon operated all patients by using Visx 20/20B excimer laser system. Age and refractive error matched patients were divided in two groups. Preoperative and five years postoperative uncorrected, best corrected visual acuity and manifest refractions were recorded to compare the out comes of both the procedures. Results: Forty eyes of 27 patients were found matched regarding age and refractive error. In PRK group among 19 patients, 12 (63.2) were male and 7 (36.8) were females whereas in Lasik group, males were equal to female patients, four each. Uncorrected postoperative visual acuity was comparable in both groups. Patients in both groups were happy regarding their visual outcome. Conclusion: PRK is as effective as Lasik for the correction of moderate degree of myopia regarding visual out come and corneal health and is cost effective.